Calcium carbonate phase change cementing material hardened body as well as preparation method and application thereof
Through radio frequency heating technology, the problem of inefficient maintenance efficiency of existing calcium carbonate phase change gelling materials has been solved, and efficient densification and strength improvement of the material has been achieved.
Patent Information
- Application Number
- CN202411264982.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-02-07
AI Technical Summary
The existing methods of calcium carbonate phase change gelling materials have low efficiency, resulting in poor mechanical properties and excessive maintenance time.
The calcium carbonate phase-change gelling material is cured by radio frequency heating, and an alternating electric field is generated through the radio frequency generator to promote the dissolution and recrystallization of calcium carbonate particles, and improve the density and strength of the material.
Radio frequency heating significantly improves the compressive strength of calcium carbonate phase-change gelling materials, shortens the curing time, and reduces heat consumption, solving the problem of uneven heating in traditional heating methods.
Smart Images

Figure CN119390103A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic non-metallic materials, and in particular relates to a calcium carbonate phase change gelling material hardened body and a preparation method and application thereof. Background Art
[0002] The development of human economic civilization is inseparable from industrial production processes such as combustion and processing, which have brought about a large amount of greenhouse gas emissions. Even though people have realized the impact of greenhouse gas emissions on the environment and are gradually taking various measures to reduce greenhouse gas emissions, the problems of global warming and ocean acidification caused by excessive greenhouse gas emissions have become ecological damage issues that cannot be ignored. Carbon dioxide accounts for a huge proportion of greenhouse gases, and excessive carbon dioxide emissions caused by industrial production are considered to be one of the main causes of a series of greenhouse effects. Carbonate rocks are estimated to contain about 39,000,000 Gt of terrestrial CO2, providing a potential way for the stable long-term storage of CO2 generated by human activities. In addition, carbonate rocks, such as limestone and marble, are mainly composed of calcium carbonate (CaCO3) and have long been widely used by humans as building materials, which provides a potential solution for recycling CO2 into value-added materials.
[0003] Carbon capture, utilization and storage technology combines CO2 capture, transportation and storage, and re-applies carbon emissions in the production process to production. It is widely regarded as one of the powerful means to solve excessive carbon dioxide emissions and achieve renewable recycling. The secondary carbonate minerals in the strata are in line with the mineral storage mechanism in carbon capture and storage. Calcium carbonate is a very important inorganic non-metallic material and industrial raw material with the characteristics of low price, wide source, easy processing, and controllable morphology. Calcium carbonate mainly has the following common crystal forms: aragonite, calcite, vaterite, amorphous calcium carbonate, etc. From the perspective of thermodynamic stability, calcite is the most stable, with a large number and a wide range of sources. Amorphous calcium carbonate is thermodynamically less stable than calcite. Since there are many types of calcium carbonate crystal forms and the transformation is easy to control, the main method for preparing calcium carbonate block materials is to control the morphological characteristics of calcium carbonate crystals by controlling the transformation of calcium carbonate crystal forms.
[0004] Among the various calcium carbonate crystal forms currently available in the calcium carbonate phase change cementitious materials, the one with a large amount of vaterite accumulated and a small amount of aragonite interspersed and spliced has better mechanical properties. The reason is that vaterite is spherical and aragonite is needle-rod-shaped. The needle-rod-shaped vaterite interspersed with the spherical accumulation forms a three-dimensional network structure with cementing force, which can form a calcium carbonate hardened body with certain mechanical strength.
[0005] At present, the main curing method of calcium carbonate phase change cementitious materials is to accelerate the formation of three-dimensional network structure by steaming with water. Under the action of water, the free energy of calcium carbonate transformation and interface energy are reduced, which promotes the crystal transformation and interface fusion of calcium carbonate, and the morphology of calcium carbonate changes by dissolution and recrystallization. The samples obtained by this method have high porosity, poor mechanical properties, and the curing time is too long. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a calcium carbonate phase change cementitious material hardened body and a preparation method and application thereof.
[0007] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a hardened body of a calcium carbonate phase change gelling material comprises the following steps: First, vaterite and a crystal modifier are mixed evenly, and then water is added and stirred to obtain a slurry. After the slurry is formed, radio frequency heating and curing are performed. The frequency of the radio frequency heating is 300KHz~300GHz and the power is 500~900W. After the radio frequency heating and curing, the calcium carbonate phase change cementitious material hardened body is prepared.
[0008] Preferably, the mass ratio of the vaterite to the crystal form regulator is 30-80:20-60.
[0009] Preferably, the crystal form regulator includes at least one of aragonite minerals, magnesium-containing phase minerals and strontium-containing phase minerals.
[0010] The average aspect ratio of the aragonite in the aragonite mineral is 5-40; the magnesium content of the magnesium-containing phase mineral is not less than 45% calculated in the form of magnesium oxide; the strontium content of the strontium-containing phase mineral is not less than 35%. More preferably, the average aspect ratio of the aragonite in the aragonite mineral is 8-12; the magnesium content of the magnesium-containing phase mineral is not less than 50% calculated in the form of magnesium oxide; the strontium content of the strontium-containing phase mineral is not less than 40%.
[0011] Preferably, the aragonite mineral is at least one of aragonite whiskers, coral powder and shell powder; the magnesium-containing phase mineral is at least one of chlormagnesia ore powder, kieserite ore powder and dolomite ore powder; the strontium-containing phase mineral includes at least one of celestite, strontium ore powder and strontium-rich aragonite ore powder.
[0012] Preferably, in the crystal modifier, the content of the aragonite mineral is not less than 40wt%, and the total content of the magnesium-containing phase mineral and the strontium-containing phase mineral is not less than 20wt%. More preferably, the content of the aragonite mineral is not less than 50wt%, and the total content of the magnesium-containing phase mineral and the strontium-containing phase mineral is not less than 25%.
[0013] Preferably, the crystal form regulator further comprises a supporting agent, wherein the supporting agent is at least one of graphene nitride, graphene boride and graphene oxide. The supporting agent is used to enhance the stability and performance of the crystal form regulator.
[0014] Preferably, the crystal form regulator is prepared according to the following method: the components are ground and heat treated and then mixed evenly. The average particle size of the prepared crystal form regulator is 30-80 μm and the water content is less than 3.00%; more preferably, the average particle size is 30-50 μm and the water content is less than 2.00%.
[0015] Preferably, the molding method is one of extrusion molding, casting molding and compression molding, wherein the compression molding pressure is 50-150 MPa, more preferably 75-125 MPa.
[0016] Preferably, the frequency of the RF heating should match the thickness of the heated object. Taking the heating object with a thickness of 2.00 cm as an example, the frequency should be 300 MHz-1 GHz, preferably 500 MHz-600 MHz, and the power of the RF heating is 650-750 W.
[0017] Preferably, the RF heating curing time is 15 to 150 minutes, more preferably 60 to 120 minutes. After the RF heating curing, the final temperature of the sample is 60 to 100°C.
[0018] The calcium carbonate phase change gelling material hardened body is prepared by the method for preparing the calcium carbonate phase change gelling material hardened body.
[0019] The hardened calcium carbonate phase change cementitious material is used as a building material, and further, as a brick and board in a building material; and further, as a marine construction material, it has a good effect of resisting seawater erosion.
[0020] The mechanism involved in the present invention: The present invention uses radio frequency heating to maintain the calcium carbonate phase change gelling material (including vaterite and crystal form regulator), by applying a high voltage alternating electric field to a medium sandwiched between two parallel electrodes, generating heat through a radio frequency generator, and the radio frequency generator generates an electromagnetic (EM) energy oscillation field, so that the dipoles rotate (that is, when polar molecules try to respond to the applied alternating electric field and arrange themselves and interact with adjacent molecules, causing lattice and friction losses when they rotate) and the resistance heating generated by the dipole rotation is combined to complete. In this way, the problem of rapid heating of poor conductors is solved by means of an external field, which is more suitable for the heating and maintenance process of the calcium carbonate phase change material. And based on the characteristics of high radio frequency and wavelength, the electromagnetic waves in the radio frequency spectrum can penetrate deeper into the calcium carbonate phase change gelling material, achieving uniform heating, reducing heat consumption, and reducing the effect of heating time. The energy of the electromagnetic waves generated by radio frequency can be better absorbed by the water medium in the calcium carbonate phase change cementitious material, promoting the dissolution and recrystallization process of calcium carbonate particles and reducing energy dissipation. The interaction between electromagnetic radiation and the strong electromagnetic field of the solution is conducive to the accumulation of vaterite particles and the formation of aragonite crystals, which can guide the growth of crystals, promote the intersection of crystal structures, and make the structure dense. The addition of crystal form regulators provides seeds for the crystal form transformation process of vaterite, reducing the potential energy of crystal form transformation. The introduction of magnesium and strontium minerals reduces the occurrence of side reactions of the transformation of vaterite to calcite crystal form through the stabilization of the vaterite crystal form by magnesium and strontium ions. In addition, the introduction of structural support additives optimizes the contact structure between the crystal form regulator and the reaction raw materials, promoting the regulation effect.
[0021] Compared with the prior art, the beneficial effects of the present invention include: Most traditional rapid heating methods have high requirements for the conductivity of materials. Through inductive eddy currents, the resistance loss is efficiently converted into heat energy for direct heating. However, as a poor conductor, calcium carbonate phase change cementitious materials cannot be heated by traditional rapid heating methods. They can only be heated indirectly by water vapor and other methods, resulting in unnecessary heat loss during the propagation process, low efficiency, and long time consumption. In addition, the heat applied by water vapor can only be absorbed by the surface of the test block and then propagated to the inside, which easily leads to uneven heating. Radio frequency heating is different from the traditional heat source directly contacting the medium for heat conduction. On the one hand, radio frequency heating uses the alternating electric field to affect the resistance to achieve heating. Compared with the traditional steam curing method, it greatly improves the heat exchange efficiency and greatly reduces the curing time from the initial product to the finished product, solving the problem of greater processing difficulty caused by the poor thermal conductivity of vaterite. On the other hand, the characteristics of radio frequency electromagnetic waves are used to promote the crystal transformation from the microstructure, induce the crystal growth direction, and then promote the intersection of crystal structures, making the structure dense, and finally achieving a relatively short time. Reduce heat consumption while greatly improving the strength of the finished calcium carbonate phase change cementitious material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 1.
[0023] Figure 2 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 2.
[0024] Figure 3 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 3.
[0025] Figure 4 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Comparative Example 1.
[0026] Figure 5 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Comparative Example 2.
[0027] Figure 6 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 4.
[0028] Figure 7 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 5.
[0029] Figure 8 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Comparative Example 3. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The vaterite used in the examples and comparative examples of the present invention was prepared by a precipitation method.
[0032] The preparation process of the aragonite whisker is as follows: by slowly adding a Na2CO3 solution to a mixed solution of CaCl2 and MgCl2, the solution system Na + , Ca 2+ Mg 2+ The molar ratio is 2:1:0.1, Ca 2+ The concentration is 0.05~0.1mol / L, and the system is placed in a constant temperature water bath at 80℃. After the addition is completed, the solution is filtered after reacting for 3 hours. The product is washed with distilled water for 4~5 times and then placed in a 60℃ oven for drying for 12 hours and then taken out to obtain aragonite whiskers.
[0033] The preparation method of vaterite is as follows: after mixing 1.5 mol / L of equal volumes and concentrations of calcium chloride dihydrate and anhydrous potassium carbonate, the precipitate is filtered, the filter cake is washed with deionized water and anhydrous ethanol and then dried, and dried at 60° C. for 24 hours.
[0034] The vaterite product was characterized by XRD, and the purity of the vaterite was 99.13%.
[0035] The crystal form modifiers used in the embodiments and comparative examples of the present invention are divided into category 1 and category 2, wherein Category 1: The content of coral powder is 57%, and the average aspect ratio of aragonite is 5.77; the content of magnesite powder is 12%, and the mineral magnesium content is 58% calculated in the form of magnesium oxide; the content of celestite powder is 9%, and the mineral strontium content is 42%; the structural support component uses graphene oxide aqueous dispersion, the specification is 1mg / ml, and the content is 22%. After the coral powder, magnesite powder, and celestite powder are ground and heat-treated at 220℃ for 10min in air atmosphere, they are mixed with graphene oxide aqueous dispersion and dried at 60℃ for 8h. The average particle size of the obtained crystal form regulator is 35μm and the water content is 1.53%.
[0036] Category 2: The content of coral powder is 57%, and the average aspect ratio of aragonite is 11.43; the content of magnesite powder is 15%, and the mineral magnesium content is 62% calculated in the form of magnesium oxide; the content of strontium-containing mineral celestite powder is 13%, and the mineral strontium content is 44%; the structural support component uses graphene oxide aqueous dispersion, the specification is 1mg / ml, and the content is 15%. After the coral powder, magnesite powder, and celestite powder are ground and heat-treated at 220℃ for 10min in air atmosphere, they are mixed with graphene oxide aqueous dispersion and dried at 60℃ for 8h. The average particle size of the obtained crystal form regulator is 47μm and the water content is 1.73%.
[0037] Example 1 A method for preparing a hardened body of a calcium carbonate phase change cementitious material, comprising the following steps: 60 parts by mass of vaterite and 40 parts by mass of category 1 crystal form regulator were mixed in a stirring pot. After stirring for 5 minutes, water was mixed with the solid raw material at a water-to-solid ratio of 0.35 to obtain a calcium carbonate phase change cementitious material slurry. The slurry was poured into a stainless steel cylindrical mold with a diameter of 20 mm, and pressurized using an automatic press with a molding pressure of 100 MPa. After pressurization for 2 minutes, the mold was demolded to obtain a test block with a height of 20 mm and a diameter of 20 mm. The test block was placed in a radio frequency environment for curing for 15 minutes (the radio frequency frequency was 500 MHz-600 MHz) and the radio frequency heating power was 700 w to obtain a hardened calcium carbonate phase change cementitious material.
[0038] Example 2 A method for preparing a hardened body of a calcium carbonate phase change cementitious material, comprising the following steps: 60 parts by mass of vaterite and 40 parts by mass of category 1 crystal form regulator were mixed in a stirring pot. After stirring for 5 minutes, water was mixed with the solid raw material at a water-to-solid ratio of 0.35 to obtain a calcium carbonate phase change cementitious material slurry. The slurry was poured into a stainless steel cylindrical mold with a diameter of 20 mm, and pressurized using an automatic press with a molding pressure of 100 MPa. After pressurization for 2 minutes, the mold was demolded to obtain a test block with a height of 20 mm and a diameter of 20 mm. The test block was placed in a radio frequency environment for curing for 30 minutes (the radio frequency frequency was 500 MHz-600 MHz) and the radio frequency heating power was 700 w to obtain a hardened calcium carbonate phase change cementitious material.
[0039] Example 3 A method for preparing a hardened body of a calcium carbonate phase change cementitious material, comprising the following steps: 60 parts by mass of vaterite and 40 parts by mass of category 1 crystal form regulator were mixed in a stirring pot. After stirring for 5 minutes, water was mixed with the solid raw material at a water-to-solid ratio of 0.35 to obtain a calcium carbonate phase change cementitious material slurry. The slurry was poured into a stainless steel cylindrical mold with a diameter of 20 mm, and pressurized using an automatic press with a molding pressure of 100 MPa. After pressurization for 2 minutes, the mold was demolded to obtain a test block with a height of 20 mm and a diameter of 20 mm. The test block was placed in a radio frequency environment for curing for 45 minutes (the radio frequency frequency was 500 MHz-600 MHz) and the radio frequency heating power was 700 w to obtain a hardened calcium carbonate phase change cementitious material.
[0040] Example 4 A method for preparing a hardened body of a calcium carbonate phase change cementitious material, comprising the following steps: 60 parts by mass of vaterite and 40 parts by mass of category 2 crystal form regulator are mixed in a stirring pot. After stirring for 5 minutes, water is mixed with the solid raw material at a water-to-solid ratio of 0.35 to obtain a calcium carbonate phase change cementitious material slurry. The slurry is poured into a stainless steel cylindrical mold with a diameter of 20 mm, and pressurized using an automatic press with a molding pressure of 100 MPa. After pressurization for 2 minutes, the mold is demolded to obtain a test block with a height of 20 mm and a diameter of 20 mm. The test block is placed in a radio frequency environment for curing for 30 minutes. The radio frequency range is 500 MHz-600 MHz, and the radio frequency heating power is 700 w to obtain a hardened calcium carbonate phase change cementitious material.
[0041] Example 5 A method for preparing a hardened body of a calcium carbonate phase change cementitious material, comprising the following steps: 60 parts by mass of vaterite and 40 parts by mass of aragonite whiskers were mixed in a stirring pot. After stirring for 5 minutes, water was mixed with the solid raw material at a water-to-solid ratio of 0.35 to obtain a calcium carbonate phase change cementitious material slurry. The slurry was poured into a stainless steel cylindrical mold with a diameter of 20 mm, and pressurized using an automatic press with a molding pressure of 100 MPa. After pressurization for 2 minutes, the mold was demolded to obtain a test block with a height of 20 mm and a diameter of 20 mm. The test block was placed in a radio frequency environment for curing for 30 minutes. The radio frequency range was 500 MHz-600 MHz, and the radio frequency heating power was 700 w to obtain a hardened calcium carbonate phase change cementitious material.
[0042] Comparative Example 1 A method for preparing a hardened body of a calcium carbonate phase change cementitious material, comprising the following steps: 60 parts by mass of vaterite and 40 parts by mass of category 1 crystal form regulator were mixed in a stirring pot. After stirring for 5 minutes, water was mixed with the solid raw material at a water-to-solid ratio of 0.35 to obtain a calcium carbonate phase change cementitious material slurry. The slurry was poured into a stainless steel cylindrical mold with a diameter of 20 mm, and pressurized using an automatic press with a molding pressure of 100 MPa. After pressurization for 2 minutes, the mold was demolded to obtain a test block with a height of 20 mm and a diameter of 20 mm. The test block was placed in a steam environment at a temperature of 60°C for curing for 3 days to obtain a hardened calcium carbonate phase change cementitious material.
[0043] Comparative Example 2 A method for preparing a hardened body of a calcium carbonate phase change cementitious material, comprising the following steps: 60 parts by mass of vaterite and 40 parts by mass of category 1 crystal form regulator were mixed in a stirring pot. After stirring for 5 minutes, water was mixed with the solid raw material at a water-to-solid ratio of 0.35 to obtain a calcium carbonate phase change cementitious material slurry. The slurry was poured into a stainless steel cylindrical mold with a diameter of 20 mm, and pressurized using an automatic press with a molding pressure of 100 MPa. After pressurization for 2 minutes, the mold was demolded to obtain a test block with a height of 20 mm and a diameter of 20 mm. The test block was placed in a steam environment at a temperature of 100°C for curing for 3 days to obtain a hardened calcium carbonate phase change cementitious material.
[0044] Comparative Example 3 A method for preparing a hardened body of a calcium carbonate phase change cementitious material, comprising the following steps: 60 parts by mass of vaterite and 40 parts by mass of category 1 crystal form regulator are mixed in a stirring pot. After stirring for 5 minutes, water is mixed with the solid raw material at a water-to-solid ratio of 0.35 to obtain a calcium carbonate phase change cementitious material slurry. The slurry is poured into a stainless steel cylindrical mold with a diameter of 20 mm, and pressurized using an automatic press with a molding pressure of 100 MPa. After pressurization for 2 minutes, the mold is demolded to obtain a test block with a height of 20 mm and a diameter of 20 mm. The test block is placed in a radio frequency environment for curing for 45 minutes. The radio frequency range is 10 MHz-20 MGHz, and the radio frequency heating power is 700 w to obtain a hardened calcium carbonate phase change cementitious material.
[0045] Performance Testing 1) The compressive strength of the hardened calcium carbonate phase change cementitious materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 was tested using an electronic universal testing machine at a loading speed of 1 mm / min.
[0046] 2) The aragonite content and vaterite content of the hardened calcium carbonate phase change cementitious materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were tested. The relative content between the aragonite content and the vaterite content was obtained by quantitative analysis based on XRD, and the relative content refers to the sum of the two being 100%, and does not represent the actual content.
[0047] The test results are recorded in Table 1.
[0048] Table 1 Test results of Examples 1 to 5 and Comparative Examples 1 to 3
[0049] Referring to Table 1, the compressive strength of the hardened calcium carbonate phase change cementitious material obtained in Examples 1 to 5 is higher than that in the comparative example. It can be seen that the method of curing the calcium carbonate phase change cementitious material by radio frequency heating in the present invention can better promote the accumulation of the calcium carbonate phase change cementitious material precursor and partial conversion to the target mineral aragonite, and make the interface fuse and bond, thereby significantly improving the compressive strength, compared with steam curing.
[0050] Specifically, Figure 1 This is a SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 1. Figure 2 This is a SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 2. Figure 3 This is a SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 3. Figure 4 This is the SEM image of the hardened body of the calcium carbonate phase change cementitious material of Comparative Example 1. Figure 5 This is a SEM image of the hardened body of the calcium carbonate phase change cementitious material of Comparative Example 2. Figures 1 to 5As can be seen in, in Comparative Example 1, only part of the phase change occurs in vaterite, and the interface of most of the surface regions is distinct, and the connection is not tight, and its hardened body has poor cohesiveness, high porosity, and low compressive strength. Comparative Example 2 is improved compared to Comparative Example 1, but is better than nothing. Compared with Comparative Example, the effect that embodiment 1 ~ 3 promotes the accumulation of vaterite structure, the generation of needle-rod aragonite structure is better, and the intergranular interface fuses and bonds, and then the compressive strength of hardened body is higher.
[0051] Figure 6 This is a SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 4. Figure 7 This is a SEM image of the hardened body of the calcium carbonate phase change cementitious material of Example 5. Figure 8 This is a SEM image of the hardened body of the calcium carbonate phase change cementitious material of Comparative Example 3. Figures 6-8 It can be known that embodiment 4~5 promotes the effect that vaterite structure is accumulated, needle-rod aragonite structure is generated better, and the intergranular interface fuses and bonds, and then makes the compressive strength of hardened body higher.In comparative example 3, only part of phase change occurs in vaterite, and a part of vaterite is agglomerated to form coating, and spatial structure is more inclined to mutual accumulation, and is not tightly connected, and its hardened body has poor cohesiveness, and porosity is high, and compressive strength is low.
[0052] Here, because less effective ingredients of the crystal form regulator are added in Examples 1 to 3, aragonite has been interspersed between the spherical vaterite as a connection during the phase change process, and is connected to each other as a whole, so no obvious needle-rod aragonite structure can be seen. More effective ingredients of the crystal form regulator added in Example 4 further promote the transformation of aragonite and the formation of a network structure, and the strength is higher. In Example 5, aragonite is directly introduced in the form of "aragonite whiskers", and some aragonite is not added to the network structure, so a more obvious needle-rod structure can be seen, and the strength is lower.
[0053] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a hardened calcium carbonate phase change cementitious material, characterized in that: The steps include: First, vaterite and a crystal modifier are mixed evenly, and then water is added and stirred to obtain a slurry. After the slurry is formed, radio frequency heating and curing are performed. The frequency of the radio frequency heating is 300KHz~300GHz and the power is 500~900W. After the radio frequency heating and curing, the calcium carbonate phase change cementitious material hardened body is prepared.
2. The method for preparing a hardened calcium carbonate phase change cementitious material according to claim 1, characterized in that: The mass ratio of the vaterite to the crystal form regulator is 30-80:20-60.
3. The method for preparing a hardened calcium carbonate phase change cementitious material according to claim 1, characterized in that: The crystal form regulator includes at least one of aragonite minerals, magnesium-containing phase minerals and strontium-containing phase minerals; The average aspect ratio of the aragonite in the aragonite minerals is 5-40; the magnesium content of the magnesium-containing phase minerals is not less than 45% calculated in the form of magnesium oxide; the strontium content of the strontium-containing phase minerals is not less than 35%.
4. The method for preparing a hardened calcium carbonate phase change cementitious material according to claim 3, characterized in that: The aragonite mineral is at least one of aragonite whiskers, coral powder and shell powder; the magnesium-containing phase mineral is at least one of chlormagnesia ore powder, kieserite ore powder and dolomite ore powder; the strontium-containing phase mineral includes at least one of celestite, strontium ore powder and strontium-rich aragonite ore powder.
5. The method for preparing a hardened calcium carbonate phase change cementitious material according to claim 3, characterized in that: In the crystal regulator, the content of the aragonite mineral is not less than 40wt%, and the total content of the magnesium-containing phase mineral and the strontium-containing phase mineral is not less than 20wt%.
6. The method for preparing a hardened calcium carbonate phase change cementitious material according to claim 3, characterized in that: The crystal form regulator further includes a supporting auxiliary agent, and the supporting auxiliary agent is at least one of graphene nitride, graphene boride and graphene oxide.
7. The method for preparing a hardened calcium carbonate phase change cementitious material according to claim 6, characterized in that: The crystal form regulator is prepared according to the following method: grinding and heat treating the components and then mixing them evenly. The average particle size of the prepared crystal form regulator is 30-80 μm and the water content is less than 3.00%.
8. The method for preparing a hardened calcium carbonate phase change cementitious material according to any one of claims 1 to 4, characterized in that: The amount of water added is such that the water-to-solid ratio is 0.30-0.40; The molding method is one of extrusion molding, casting molding and compression molding; The frequency of the radio frequency heating is 300MHz-1GHz, and the power is 650~750W; The radio frequency heating curing time is 15 to 150 minutes.
9. A hardened calcium carbonate phase change cementitious material obtained by the method for preparing a hardened calcium carbonate phase change cementitious material according to any one of claims 1 to 8.
10. Use of the hardened calcium carbonate phase change cementitious material according to claim 9 as a building material.
Citation Information
Cited By
Calcium carbonate thermal insulation material as well as preparation method and application thereof
CN121202172A
A calcium carbonate thermal insulation material, its preparation method and application
CN121202172B